Hubungan nilai budaya suku Batak dengan ideologi patriarki pada karakter pria dalam film Ngeri-Ngeri Sedap - Laluna, Fadila Rana; Suryadi, Muhammad; Waluyo, Sukarjo; Sahertian, Michael Kevin Bryan (Universitas Mulawarman, 2024)
This research was carried out to understand the relationship between Batak cultural values and patriarchal ideology, which is reflected in the masculinity of the male characters (Mr. Domu, Domu, Gabe, and Sahat) in the film Ngeri-Ngeri Sedap, directed by Bene Dion Rajagukguk. This research was carried out based on interpreting the emerging patriarchal ideology in the film Ngeri-Ngeri Sedap through signs of masculinity of male characters who live in Toba, North Sumatra, or those who choose to emigrate. The method used in this research is a qualitative approach through the sociology of literature and gender (masculinity) and literature study. The theory used in analyzing this film is the theory of masculinity by Tuncay. The results found are that there is a relationship between patriarchal ideology, which is reflected through the masculinity of male characters in films, and Batak cultural values. Individuals who live their lives with strong Batak cultural values almost every day will have a higher level of masculinity, which will result in a stronger patriarchal ideology that they display. Meanwhile, individuals who live a life with strong Batak cultural values will show less of their patriarchal ideology to those around them.